MODEL IDEAL PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN KREATIVITAS SISWA KELAS X MIA MAN 1 KOTA TERNATE PADA KONSEP GERAK LURUS DENGAN KECEPATAN DAN PERCEPATAN KONSTAN - Nasrun Balulu; Rukia M. Jum (Universitas Khairun, 2020)
The Ideal Problem Solving model is designed to help to identify and understand the problem solving to practice the ability of creativity to describe the systematic procedure of the word “Ideal” and is used to guide teachers to help students how to identify problems, define goals, explore exploration strategies, anticipate the results and act and see and learn. This research is experimental. This research aims to find out the increase in students 'creativity ability in learning straight-motion material with constant speed and acceleration and find out the consistency of increasing students' creative ability. The research subjects were 62 students MIA-1 and MIA-2 Madrasah Aliyah Negeri 1 Ternate. This research is quantitative descriptive research methods with One Group Pre-Test and Post-Test design, the variables used in this study were independent namely the Ideal Problem Solving Model, and the dependent variable increase students ' creative ability. The Technique of collecting data in this research is the observation of student activities, Creativity Tests, and questionnaires. The instruments are in the form of essay questions, consist of 7 items that have been tested, the N-Gain formula was used to calculate students' creative abilities, through the Pre-test with the lowest average score is 27 in the MIA-1 class and the Post-test with an average score is 70, for the MIA-2 class through the Pre-test with the lowest average score is 30 and through the Post-test with an average score is 72. Research results show that an increase in students' creative abilities after applying the IDEAL Problem Solve learning model with N-Gain 62% for MIA-1 and 61% for MIA-2 moderate category, after an increase in creativity is observed, it is tested using the Cooperative Test or the two-party Test (t) to see the consistency of differences, the results of the study showed that t-count <t-table or 0.09 <2,000 and there is no consistent difference in increasing the ability of creativity after applying the IDEAL Problem Solving model.